Penerapan Metode Muyassar Dalam Peningkatan Pemahaman Pembelajaran Al-Qur’an Pada Anak - Miftah Syarif; Ida Windi Wahyuni; Alucyana Alucyana; Raihana Raihan (Al-Mudarris, 2021)
Muyassar is a method that is arranged in an applicable and effective manner, to make it easier for students to be able to read the Qur'an well in a short time, including for early childhood. The purpose of this study is to describe the application of the muyassar method in learning the Qur'an and to determine the application of the muyassar method in improving the understanding of learning the Qur'an in children. The classroom action research method (CAR) in this study used two cycles with indicators of success reaching above 75%. The research subjects were MDTA students, Nurul Ikhlas, Sungai Pagar Village, Kampar Kiri Hilir District, Kampar Regency with a total of 15 children (6 boys and 9 girls). The instrument used is the teacher and student activity observation sheet. Data collection techniques through observation, and documentation. The data analysis technique used descriptive qualitative data analysis. The application of the muyassar method has increased in understanding the learning of the Qur'an in children. The results of this study indicate that the Al-Qur'an learning activities through the Muyassar Method have been successful and there has been an increase so that students can independently learn the Qur'an through the Muyassar Method.